Policy shops, hired guns, and gatekeepers: The organization and distribution of policy analysts in Ontario. (21st November 2022) - Migone, Andrea; Howlett, Michael
Abstract: Policy professionals play an important role in political and administrative systems. However, the exact configuration and distribution of such personnel within agencies remains largely unknown. Early works noted the creation of small dedicated "policy shops" in many governments after 1960 where many policy professionals were located. Studies in Canada and elsewhere subsequently confirmed this organizational form but questions such as how many professionals are employed and where these units are located within existing departmental structures remain opaque. In this article, we provide an organizational mapping of professional policy personnel in the Ontario Public Service (OPS). We find that four major personnel distribution patterns exist within the OPS with only some analysts and professionals working in "classical" policy shops. These findings underscore the need to re‐evaluate the organization and staffing of professional policy analysts in government in order to better account for the kinds of work policy professionals do in modern administrations. Sommaire: Les professionnels des politiques jouent un rôle important dans les systèmes politiques et administratifs. Néanmoins, la configuration et la répartition exactes d'un tel personnel parmi et entre les organismes hiérarchiques et d'état‐major demeurent largement inconnues. Les premiers travaux ont noté la création de petits « ateliers de politiques » dévoués dans de nombreux gouvernements après 1960, où l'on trouvait de nombreux professionnels des politiques. Bien que des études au Canada et ailleurs ont par la suite confirmé cette caractéristique organisationnelle, certaines questions telles que le nombre de professionnels employés et l'emplacement de ces unités au sein des structures ministérielles existantes à l'époque contemporaine demeurent obscures. Dans cet article, nous fournissons une cartographie organisationnelle du personnel chargé des politiques dans la fonction publique de l'Ontario (FPO). Nous constatons qu'il existe quatre principaux modèles de répartition du personnel au sein de la FPO, avec seulement quelques analystes et professionnels travaillant dans des ateliers de politiques « classiques ». Ces résultats soulignent la nécessité de réévaluer l'organisation et le recrutement du personnel impliqué dans l'analyse professionnelle des politiques afin de mieux tenir compte des divers travaux accomplis par ces professionnels dans le gouvernement moderne.